2012
DOI: 10.1016/j.dza.2012.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing acupuncture stimuli using brain imaging with fMRI – a systematic review and meta-analysis of the literature

Abstract: Background: The mechanisms of action underlying acupuncture, including acupuncture point specificity, are not well understood. In the previous decade, an increasing number of studies have applied fMRI to investigate brain response to acupuncture stimulation. Our aim was to provide a systematic overview of acupuncture fMRI research considering the following aspects: 1) differences between verum and sham acupuncture, 2) differences due to various methods of acupuncture manipulation, 3) differences between patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(64 citation statements)
references
References 38 publications
4
55
1
4
Order By: Relevance
“…The chosen acupoints, among others, are commonly used for pain treatment in the present literature. 25 Needling was performed with 0.25 · 25-mm stainless steel needles. All needles were inserted perpendicularly, to a depth of about 1-2 cm, at LI4 and LV3 and about 2-3 cm deep at ST36 (Fig.…”
Section: Acupuncture Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…The chosen acupoints, among others, are commonly used for pain treatment in the present literature. 25 Needling was performed with 0.25 · 25-mm stainless steel needles. All needles were inserted perpendicularly, to a depth of about 1-2 cm, at LI4 and LV3 and about 2-3 cm deep at ST36 (Fig.…”
Section: Acupuncture Proceduresmentioning
confidence: 99%
“…25 Thus, some evidence already shows acupuncture-specific effects on pain, reflected by modulation in certain brain regions responsible for pain processing, but these effects are far from being established. 25 Many of the magnetic resonance imaging (MRI) studies on acupuncture so far have focused on the direct effects of the needling procedure of acupuncture, either alone or in an ongoing pain process with a standardized pain stimulus. The current trial studied the effects of acupuncture on subsequent individualized pain stimuli.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Brain imaging studies have shown that acupuncture alters activation patterns in brain areas associated with pain processing [9]. It is postulated that in response to the needle stimulation mechanisms of the endogenous pain modulation such as diffuse noxious inhibitory controls (DNIC), segmental inhibition, and descending pain control pathways lead to a decrease in pain perception [10,11].…”
Section: Introductionmentioning
confidence: 99%